Analisis Kinerja Keuangan Perusahaan Kosmetik yang Terdaftar di Bursa Efek Indonesia Menggunakan Rasio Keuangan - Nur Hudaya Abdullah; Agung Widhi Kurniawan; Nurman (Indonesian Journal of Economics, Entrepreneurship, and Innovation, 2023)
This study aims at analyzing financial performance of cosmetics company registered at Indonesia stock exchange during Covid-19 pandemic. In analyzing the financial performance of the cosmetics company, financial ratios including liquidity ratio, solvency ratio, activity ratio, and profitability ratio were applied. This study analyzes 3 giant cosmetics companies namely PT. AWI, PT. KNI, and PT. UNI (all names are pseudonymized). This study finds that (1) PT. AWI and PT. KNI have good performance in terms of liquidity ratio analysis; (2) PT. AWI and PT. KNI show good performance in terms of solvency ratio; (3) PT. UNI outperforms the other two cosmetics companies in terms of activity ratio analysis; (4) PT. AWI and PT. UNI outperform another cosmetics company in terms of analysis of profitability ratios; and (5) PT. UNI outperforms the other two cosmetics company in terms of the return on assets and the return on equity. This study draws findings and valuable conclusion which descriptively describes the actual phenomenon which are expected to be beneficial for further researchers.